Relationship between sense of coherence and subjective well-being among family caregivers of breast cancer patients: a latent profile analysis - Wang, Hui; Wu, Yuxia; Huang, Xuefang; Yan, Haiou (Frontiers in Psychiatry, 2025)
ObjectiveSense of coherence (SOC) assists cancer-affected caregivers in overcoming challenges in the process of caregiving and may potentially influence an individual’s subjective well-being (SWB). This study aimed to explore distinct SOC profiles among caregivers of breast cancer patients, identify the distribution differences of these profiles in sociodemographic and clinical characteristics, and explore their relationship with SWB.MethodsA total of 360 patients with caregivers of breast cancer patients from one tertiary hospitals in Jiangsu completed the Sociodemographic and clinical characteristics, the Sense of Coherence Scale (SOC-13), and the General Subjective Well-Being Schedule (GWB). Mplus 8.3 for latent profile was performed to identify SOC classes. Multivariate logistic regression was used to analyze the impact of various factors on the different categories, and ANOVA was applied to compare the SWB among caregivers of different categories.ResultsThree latent profiles of SOC were identified: the “low sense of coherence-meaning group” (7.9%), the “moderate sense of coherence-manageability group” (37.3%), and the “high sense of coherence-optimism group” (54.7%). Age, residence, health status, financial pressure, caregiving duration, and breast cancer stage significantly influenced the distribution of SOC in caregivers of breast cancer patients. The SWB level differed significantly among these three categories.ConclusionThis study identified three distinct classes of SOC among caregivers. It is recommended that health care providers screen caregivers with diverse profiles of SOC and pay more attention to young, rural, long-term caregiving duration, heavy economic burden, and caregivers in poor physical condition.